Study The Molarity Influence on the structural properties of titanium oxide (TiO2) Prepared with (Sol_Gel) - Riyadh sami; Rafea A. Munef; Fares Saleh Atallah (Tikrit Journal of Pure Science)
This report was  conducted to study the molar effect on  structural characteristics of Titanium dioxide TiO2 ,the deposition of films on glass substrates was done by using sol gel solution with Spin-Coting method (speed =3000 rpm) during  30 sec of  the deposition where the solution have been  prepared using  Titanium hydroxyl  Material Ti[O(CH2)3(CH3)]4 and C4H11NO2 as Fixative  and Ethanol as a solvent.  we have prepared different concentrations of solution (0.05, 0.10 , 0.15, 0.20, 0.30) M ,the films have been annealing with temperature (500 °C), we have investigated the Structural characteristics using (XRD,AFM and SEM) analyses. The (XRD) results have shown that the Anatase phase is the prevalent phase when the concentrations (0.05 and 0.10)M and after increase the concentration start changes gradually from Anatase phase to Rutile phase when the concentration (0.2)M. The  SEM analyses have approved that the film has good topography. The granules had a rhombus form then its shape became cluster with the increasing of concentration . The (AFM) have shown that the membranes had nano- thickness,and they  are soft with good coating